Kepemimpinan Komsel, Sikap Hidup Kristiani, dan Pemuridan sebagai Prediktor Pertumbuhan Jemaat: Kajian Empiris di Christian Ministry Church Jakarta - Johan Juliawan Adhi; Matheus Mangentang; Stenly Reina Paparang (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2026)
This article examines the influence of cell group (komsel) leadership, Christian lifestyle, and discipleship on the growth of the congregation at Christian Ministry Church (CMC) Jakarta. Employing a quantitative correlational design with 140 respondents, the study operationalizes three independent variables (X₁ = cell leadership; X₂ = lifestyle; X₃ = discipleship) against the dependent variable (Y = congregational growth). Pearson correlation analysis reveals significant correlations between cell leadership and lifestyle (r = .800, p < .01) and between cell leadership and discipleship (r = .591, p < .01), whereas direct correlations with Y were non-significant individually. Multiple regression yielded R = .752 and R² = .566, indicating that collectively the three predictors account for 56.6% of variance in congregational growth. These findings reinforce the argument that organic church growth is multidimensional and that the synergistic interaction of cell leadership, moral integrity, and discipleship constitutes a coherent growth ecosystem. Theological and pastoral implications are discussed within frameworks of contemporary missiology and cell ecclesiology.